The underlying pathological mechanism of ferroptosis in the development of cardiovascular disease - Zhang, Li-Li; Tang, Rui-Jie; Yang, Yue-Jin (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVDs) have been attracting the attention of academic society for decades. Numerous researchers contributed to figuring out the core mechanisms underlying CVDs. Among those, pathological decompensated cellular loss posed by cell death in different kinds, namely necrosis, apoptosis and necroptosis, was widely regarded to accelerate the pathological development of most heart diseases and deteriorate cardiac function. Recently, apart from programmed cell death revealed previously, ferroptosis, a brand-new cellular death identified by its ferrous-iron-dependent manner, has been demonstrated to govern the occurrence and development of different cardiovascular disorders in many types of research as well. Therefore, clarifying the regulatory function of ferroptosis is conducive to finding out strategies for cardio-protection in different conditions and improving the prognosis of CVDs. Here, molecular mechanisms concerned are summarized systematically and categorized to depict the regulatory network of ferroptosis and point out potential therapeutic targets for diverse cardiovascular disorders.